2000
DOI: 10.1021/jp992768f
|View full text |Cite
|
Sign up to set email alerts
|

Chain Length Effect on the Structure and Photoelectrochemical Properties of Self-Assembled Monolayers of Porphyrins on Gold Electrodes

Abstract: Disulfides, with a systematic series of alkyl spacers containing porphyrins at both terminals, were prepared to investigate the effect of the spacer length on the structure and photoelectrochemical properties of self-assembled monolayers (SAMs) of the porphyrins on a gold electrode. The structure of the SAMs was studied using ultraviolet (UV)−visible absorption spectroscopy in transmission mode, cyclic voltammetry, UV−visible ellipsometry, and fluorescence spectroscopy. These measurements showed that as the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
162
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(174 citation statements)
references
References 38 publications
11
162
1
Order By: Relevance
“…This difference is probably due to a decrease of the dielectric constant in the diffuse monolayer when compared to that of the bulk solution. 16 Interestingly, a significant shift in the half-wave potential was found switching from 1 (E 1/2 = +0.145 V vs. FcH/FcH + ) to 2 (E 1/2 = +0.185 V vs. FcH/FcH + ) due to the introduction of 1-butanethiol. As for ZnTFcP-containing monolayers ( Fig.…”
Section: 11mentioning
confidence: 95%
See 1 more Smart Citation
“…This difference is probably due to a decrease of the dielectric constant in the diffuse monolayer when compared to that of the bulk solution. 16 Interestingly, a significant shift in the half-wave potential was found switching from 1 (E 1/2 = +0.145 V vs. FcH/FcH + ) to 2 (E 1/2 = +0.185 V vs. FcH/FcH + ) due to the introduction of 1-butanethiol. As for ZnTFcP-containing monolayers ( Fig.…”
Section: 11mentioning
confidence: 95%
“…Meso-arylporphyrins are well-known sensitizers for photocurrent generation and several papers have reported their properties. 16,18 Imahori and Fukuzumi 18 showed that an electron transfer can occur from an electron donor (TEOA = triethanolamine) and the singlet excited state of such porphyrins. Although electrochemical experiments were carried out in a different solvent/electrolyte system, we took into account the oxidation potential measured for 2, i.e.…”
Section: 11mentioning
confidence: 99%
“…Energy transfer from chromophores to nearby metal particles and films has been observed. [47][48][49][50][51][52] For example, we showed that in a gold break junction reversibility of single molecule isomerization was blocked.…”
Section: 46mentioning
confidence: 97%
“…However, SAM-based fluorescent sensors development has encountered difficulties due to an efficient fluorescent quenching by the metal surfaces. 202,203 Only few reports have been published on the detection of fluorescence from selfassembled monolayers on gold. Motesharei and Myles reported in 1998 the preparation of layers of a fluorescent isophthalic acid adsorbate on gold.…”
Section: Glass and Gold Surfacesmentioning
confidence: 99%